(untitled) (Research, Society and Development, 2023)
Objective: To know which and how environmental changes interfere with the control and treatment of malaria in Brazil. Methodology: This is an integrative literature review of articles in Portuguese in the databases Periodicals of BVS, Scielo and Arca Fiocruz. Results: 115 articles were found, which, after applying the filters, exclusion criteria, reading the titles and abstracts, left 3 for analysis and discussion. Discussion: human interference in the environment contributes to the alteration of the environment and the creation of conditions that favor an increase in the number of cases of malaria in the Amazon region, where mining activities stand out, with emphasis on small prospecting, deforestation, the installation of hydroelectric plants and large population migrations. Such conditions contribute to the formation of favorable environments for the proliferation and dissemination of malaria vector mosquitoes, making its control a challenge for health services, since actions also need to have an eye on environmental health. Conclusion: The results confirm the existence of an association between human interference in the environment and its relationship with the increase in cases of malaria in Brazil, especially in the Amazon region. Among the prevalent interferences, deforestation, mining (garimpo), the installation of hydroelectric plants and large population migrations stood out.